2020
DOI: 10.1155/2020/9657380
|View full text |Cite
|
Sign up to set email alerts
|

The PPARΩPocket: Renewed Opportunities for Drug Development

Abstract: The past decade of PPARγ research has dramatically improved our understanding of the structural and mechanistic bases for the diverging physiological effects of different classes of PPARγ ligands. The discoveries that lie at the heart of these developments have enabled the design of a new class of PPARγ ligands, capable of isolating central therapeutic effects of PPARγ modulation, while displayin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
7
0

Year Published

2021
2021
2025
2025

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 248 publications
(458 reference statements)
1
7
0
Order By: Relevance
“…As a phosphoprotein, PPARα can also be activated through post-translational modification. The phosphorylation sites in PPARα include Ser12, Ser21, Ser179, and Ser230 ( 83 87 ). The increased transactivation of PPARα may occur via decreased co-repressor interaction, such as NCoR, or increased interaction with co-activators, such as Peroxisome proliferator-activated receptor gamma coactivator 1-alpha (PGC-1α) ( 88 ).…”
Section: Peroxisome Proliferator-activated Receptors (Ppars) Regulationmentioning
confidence: 99%
“…As a phosphoprotein, PPARα can also be activated through post-translational modification. The phosphorylation sites in PPARα include Ser12, Ser21, Ser179, and Ser230 ( 83 87 ). The increased transactivation of PPARα may occur via decreased co-repressor interaction, such as NCoR, or increased interaction with co-activators, such as Peroxisome proliferator-activated receptor gamma coactivator 1-alpha (PGC-1α) ( 88 ).…”
Section: Peroxisome Proliferator-activated Receptors (Ppars) Regulationmentioning
confidence: 99%
“…As is known to all, PPAR γ demonstrated significant functions in the tissue protection and repair [ 22 24 ]. And advances in PPAR ligands and agonists renew opportunities for drug development [ 25 ]. Here, in our present study, we found that the activation of PPAR γ could confer hepatoprotective effects against hepatic IR injury and also investigated the therapeutic potential of PPAR γ agonists for the protection of hepatic injury.…”
Section: Discussionmentioning
confidence: 99%
“…12,15−17 Drugs developed with the aid of these standard screens remain first-line therapies in human diseases such as cancer, 14 obesity, and diabetes. 18,19 Liver receptor homolog-1 (LRH-1, NR5A2) is a nuclear receptor expressed mainly in the liver, 20−24 pancreas, 20,25,26 and gut 27−32 of adult mammals. A wide variety of chemical, genetic, and physiological studies have provided preclinical evidence that LRH-1 is a drug target with a high potential therapeutic value in type 2 diabetes, nonalcoholic fatty liver disease, and nonalcoholic steatohepatitis, 33−35 as well as pancreatic cancer and colorectal cancer, 8,25,36,37 all diseases with substantial unmet clinical need.…”
Section: ■ Introductionmentioning
confidence: 99%
“…This standard model of nuclear receptor regulation has been validated in many receptors through structural and functional studies and represents a rigorously tested, well-accepted regulatory model for this group of transcription factors. Based on this standard model, high-throughput compound screens have demonstrated outstanding effectiveness. These screens monitor the physical interaction between a nuclear receptor LBD and an LXXLL-motif containing peptide from biologically relevant transcriptional coregulators. , Drugs developed with the aid of these standard screens remain first-line therapies in human diseases such as cancer, obesity, and diabetes. , …”
Section: Introductionmentioning
confidence: 99%